An Analysis of Juvenile Delinquency in Lauren Oliver’s vanishing girls novel: An Analysis of Juvenile Delinquency in Lauren Oliver’s vanishing girls novel - pohan, annisaoktriulinah (IJOLTL (Indonesian Journal of Language Teaching and Linguistics), 2023)
This thesis is titled "An Analysis of Juvenile Delinquency in Lauren Oliver's Vanishing Girls Novel". This thesis analyzed how the delinquency in the main character. The purpose of this thesis is to know and understand how it happened, to look for both types and causes of delinquency described in the novel. The main characters are Dara, they are teenagers who commit naughty acts in this novel, the cause of their mischief is one of them is broken home and lacking affection from their parents. Drunkbehavior is often done by the main character. Overall, men are still almost twice as likely to get drunk as women, which makes it interesting to look more deeply. The theory used to analyze is the Theory according to Jensen and Turner and Helms The research method by which the author collects data from novels and from several sources of articles, books, and journals related with this thesis. The results of this thesis are revealing the truth that broken home and lack of love from parents can cause delinquency on the main character.